Quality of formative assessment and virtual education at the primary level. Educational institution N° 6014. Lima - Chirinos Siclla, Cynthia Milagros (2025)
Establishing the relationship between quality in formative assessment (variable 1) and virtual education (variable 2) is the objective of this scientific study, in primary school teachers and students at IE N. 6014. Research with a quantitative, non-experimental, cross-sectional, and ordinal level approach, we used a descriptive correlational design. We used two questionnaires for each of the study variables, one for variable 1 applied to teachers and another for variable 2 applied to students, validated by the judgment of three experts and reliability by Cronbach's alpha: Variable 1 with 0.870 and variable 2 with 0.744 of confidence. Intentional sample: 42 primary school teachers. They concluded that there is a very good significant correlation (Spearman's Rho is 0.833) between the quality of formative assessment and virtual education, p-value less than 0.05. The dimensions analyzed for each variable resulted in a moderate to relatively high correlation.